PENETAPAN UKURAN SASARAN PADA LIMA UNIT PENGGERGAIIAN KAYU JATI DI JAWA TENGAH & JAWA TIMUR - Osly Rachman; Sri Rulliaty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Three teak wood sawmilis in Central Java and two in East Java have been selected for study on target aize determi- nation Using 100 board samples from each sawmill. The result was calculated using formulos for determining lumber tar get sizeThe rasult indicates that actual size produced by three sawmills were higher than target size, ranging from 0.32 mm to 2.11 mm. The actual size produced by two other sawmills was lower than the tagret size, ranging from 0.61 mm to 6.48 mnt 5.48 mm. This result indicates that target size determination is important to improve sawing efficiency.